A comparative study of the curriculum of a master's course in anesthesiology in Iran and the United States of America - Meysam Hosseini Amiri; Hassan Babamohamadi; Monir Nobahar (Journal of Medical Education Development)
Background & Objective: The field of anesthesiology is rapidly evolving in Iran, and there is a growing need to develop educational programs in this area. As such, the purpose of this research is to conduct a comparative analysis of the curriculum for master's courses in anesthesiology between Iran and the United States. Material & Methods: This comparative descriptive study was conducted in 2023. To collect the necessary data, we extracted information from the websites of the Ministry of Health, Treatment, and Medical Education of Iran and Case Western Reserve University, respectively. Once the data was collected, we analyzed it using Bereday's model, which involves four key stages: description, interpretation, juxtaposition, and comparison. Results: Based on the results of this study, it is recommended that both Iranian and American anesthesiology master's programs incorporate the principles of professional ethics in their curriculum. One major weakness of the anesthesiology master's curriculum in Iran is its focus on preparing students for careers in education and research rather than practical application in the field. However, Iran's anesthesiology major benefits from a strong foundation in both continuous and noncontinuous anesthesiology bachelor's courses. In terms of similarities, our comparative analysis of the two programs revealed that many courses offered in anesthesiology master's programs are similar, including courses on monitoring, pharmacology, and the principles of anesthesia. Conclusion: The findings of this research have important implications for enhancing the anesthesiology master's curriculum in Iran, with a focus on improving education, research, and patient care. The results suggest that there is a need to revise the curriculum to better prepare graduates for practical application and to increase the role of graduates in the care of patients. Furthermore, the insights gained from this study can be used by educational planners to revise curriculum content and evaluation methods, with the goal of enhancing the quality of anesthesiology education and training in Iran.